Enhancing Problem-Solving Skills in Science through STEM-Based Learning: A Case Study of Eighth-Grade Students at SMPN 1 Satap Wara, Indonesia - Dian Ernaningsih; Trisnawati Saduk; Mariana Sada (The Indonesian Institute of Science and Technology Research, 2026)
Developing students’ science problem-solving ability is a critical objective in contemporary STEM education. This study investigated the effect of STEM-based instruction integrated with Problem-Based Learning (PBL) on the science problem-solving abilities of eighth-grade students at SMPN 1 Satap Wara. A pre-experimental one-group pretest–posttest design was employed involving 22 students selected through total sampling. Data were collected using a validated science problem-solving test administered before and after the intervention. Descriptive statistics indicated a substantial increase in the mean score from 19.00 (SD = 8.429 in the pretest to 51.41 (SD = 8.534) in the posttest. Inferential analysis using a paired-samples t-test revealed a statistically significant improvement in students’ problem-solving abilities (p < 0.001), with a large effect size (ES = 0.785), indicating strong practical significance. The integration of STEM and PBL facilitated active engagement in authentic problem contexts, promoting critical thinking, creativity, and collaborative learning processes. Despite the overall improvement, some students did not achieve the minimum competency standard, suggesting the need for differentiated instructional support. These findings provide empirical evidence supporting the effectiveness of STEM-based instruction in enhancing science problem-solving abilities and contribute to the growing body of literature on pedagogical strategies that prepare students with essential competencies for 21st-century learning.